2009
DOI: 10.1002/ijc.24567
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 activation contributes directly to Epstein‐Barr virus–mediated invasiveness of nasopharyngeal cancer cells in vitro

Abstract: Nasopharyngeal cancer (NPC) is an Epstein-Barr virus (EBV)-associated head and neck cancer prevalent in Asia. Although with reasons not fully understood, the intrinsic invasiveness of NPC is believed to be EBV-linked. Recently, EBV was found to induce STAT3 activation. Constitutive STAT3 activation correlated with advanced clinical staging in NPC. We hypothesized that STAT3 activation by EBV directly contributes to the intrinsic invasiveness of NPC cells. Phospho-STAT3-Tyr705 was detected in high percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 37 publications
4
72
0
Order By: Relevance
“…Indeed, it is detected in more than 75% of NPC cases. Growing evidence indicates that STAT3 activation contributes to the progression and invasiveness of NPC [16][17][18] . Therefore, the activation of STAT3 provides a promising and valid target for NPC therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is detected in more than 75% of NPC cases. Growing evidence indicates that STAT3 activation contributes to the progression and invasiveness of NPC [16][17][18] . Therefore, the activation of STAT3 provides a promising and valid target for NPC therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that STAT3 is a promising molecule target for anticancer treatment and cancer prevention [14,15] . More recently, STAT3 has also been found to be activated in www.chinaphar.com Liu DB et al Acta Pharmacologica Sinica npg more than 75% of NPC cases, and this molecule plays a significant role in driving NPC progression and metastasis [16][17][18] . A recent study identified celecoxib as a novel inhibitor of STAT3 [6] .…”
Section: Introductionmentioning
confidence: 99%
“…EGFR expression and STAT3 activation are elevated in NPC, and STAT3 activation is important for the invasiveness of EBV-associated NPC, which can be blocked by STAT3 inhibitor treatment (25,26). The effects of LMP1 on EGFR, STAT3 activation, and regulation of STAT3 target genes may be important factors in the development of NPC.…”
Section: Vol 85 2011 Ebv Lmp1 Activates Pkc␦ Pathways 4405mentioning
confidence: 99%
“…HONE1-EBV cells (gift from Prof. S.W. Tsao, University of Hong Kong) are EBV positive nasopharyngeal carcinoma cell lines [21], which were cultured in RPMI-1640 (Gibco-BRL) medium supplemented with 10% FBS. Mouse monoclonal antibody (mAb) anti-Flag was purchased from Abmart (Shanghai, China) and rabbit polyclonal antibody (pAb) anti-YFP was purchased from RayBiotech.…”
Section: Methodsmentioning
confidence: 99%
“…In order to explore the physiological mechanisms of EBV natural hosting cells, the EBV-latent cells (HONE1-EBV cells), which were generated by infecting human gastric adenocarcinoma cells (AGS) and HONE1 cells with recombinant EBV genomes expressing GFP [21,54], were chosen to continue the experiments. HONE1-EBV cells were transfected with expressing plasmid pFLAG-CMV-TAP, pCMV9-3×Flag-importin β1, pFlag-kα6, pFLAG-CMV-transportin-1 or pFLAG-CMV-2, and cells were induced to undergo lytic cycle activation by transfecting with pBZLF1-HA plasmid.…”
Section: Bflf2 Binds Tap/nxf1 Importin α7 Importin β1 and Transportmentioning
confidence: 99%